2020
DOI: 10.1186/s12886-020-01561-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health-related quality of life in Chinese patients receiving treatment for neovascular age-related macular degeneration: a prospective longitudinal study

Abstract: Background: Age-related macular degeneration (AMD) is currently the leading cause of irreversible visual impairment in developed countries and seriously affects the health-related quality of life (HRQoL) of patients. However, the majority of the research in this area employs cross-sectional design; longitudinal research investigating changes in HRQoL and influencing factors is limited. The aim of this study was to use a longitudinal study design to investigate descriptive trends in HRQoL and their predictive f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…When patients’ levels of anxiety are higher, the negative effect that reduced visual acuity has on health-related quality of life is expected to be stronger. This is consistent with the current state of the art which has highlighted the potential negative and disabling effect of comorbid mental health problems on eye disease patients’ quality of life 21 , 44 , 45 . Furthermore, previous studies have identified common factors of mental health problems among eye disease patients, which help us to understand why anxiety levels might play a key role in patients’ health-related quality of life.…”
Section: Discussionsupporting
confidence: 90%
“…When patients’ levels of anxiety are higher, the negative effect that reduced visual acuity has on health-related quality of life is expected to be stronger. This is consistent with the current state of the art which has highlighted the potential negative and disabling effect of comorbid mental health problems on eye disease patients’ quality of life 21 , 44 , 45 . Furthermore, previous studies have identified common factors of mental health problems among eye disease patients, which help us to understand why anxiety levels might play a key role in patients’ health-related quality of life.…”
Section: Discussionsupporting
confidence: 90%
“…Two studies did not report change in composite NEI VFQ‐25 score, and Schroeder et al only reported composite score change after >3 years' follow‐up (Schroeder et al, 2017 ). For the other nine reports of eight study populations, all except one (Bian et al, 2020 ) described a statistically significant improvement in composite NEI VFQ‐25 score at the earliest time point measured after baseline: 1 month (Finger et al, 2013 ); 3 months (Frennesson et al, 2010 ; Inoue et al, 2014 ; Jelin et al, 2018 ; Jelin et al, 2019 ) and 6 months (Rakic et al, 2013 ; Zhu et al, 2017 ; Gomi et al, 2019 ). In three studies, the early improvement in composite NEI VFQ‐25 score was maintained during longer‐term follow‐up at 12 months (Inoue et al, 2014 ; Gomi et al, 2019 ; Jelin et al, 2019 ); in two other studies, it was not (Finger et al, 2013 ; Rakic et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bian et al found that both visual acuity in the treated eye and overall best‐corrected visual acuity (BCVA) correlated significantly with the NEI VFQ‐25 composite score at baseline, 1, 3, 6 and 12 months (Bian et al, 2020 ). This was consistent with previous, smaller studies, which reported better visual function scores associated with higher NEI VFQ‐25 scores (Inoue et al, 2014 ; Wang et al, 2015 ; Zhu et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations